Regional Differences, Distributional Dynamics and Spatial Convergence of Pharmacist Human Resources in China: A Healthcare Tiers Difference Perspective - Ding B; Zhao R; Yue X; Li D (Risk Management and Healthcare Policy)
Bo Ding,1 Run Zhao,2 Xinyi Yue,2 Dexun Li2 1Pharmacy Department, Hefei Maternal and Child Health Hospital, Hefei, People’s Republic of China; 2School of Pharmaceutical Economics and Management, Anhui University of Chinese Medicine, Hefei, People’s Republic of ChinaCorrespondence: Dexun Li, Email lidexunoo@126.comPurpose: This study aims to analyze the regional and hierarchical disparities in the distribution of pharmacist human resources in China from 2012 to 2022, with the goal of identifying underlying trends and challenges. The findings are intended to serve as a basis for optimizing the equitable and efficient allocation of pharmacist resources to better support healthcare system development.Patients and Methods: Data were collected from the China Health Statistics Yearbook and China Statistics Yearbook. The number of pharmacists per 1,000 population was selected as a measure of equity in pharmacist allocation, and Dagum’s Gini coefficient, kernel density estimation method and spatial β-convergence model were utilized to analyze the regional differences and convergence trends of pharmacist resource allocation in Chinese hospitals and primary health care organizations.Results: The findings reveal that while the overall allocation of pharmacist resources has improved, significant discrepancies remain. The mean number of hospital pharmacists was approximately twice that of primary care centers, with the most pronounced disparity observed in the central region. Regional disparities show declining trends in hospitals but widening gaps in PHCs, particularly in the eastern region. Kernel density results highlight improvements in pharmacist distribution but also reinforce advantages for High-resource provinces, especially at the hospital tier. Spatial analysis indicates significant clustering effects in pharmacist allocation, though these effects have weakened over time. Notably, absolute and conditional β-convergence trends are observed, with faster convergence rates in hospitals compared to PHCs and distinct regional variations in convergence speed.Conclusion: Since 2012, the allocation of pharmacists’ human resources in China has improved, with regional disparities showing signs of reduction. However, hierarchical disparities remain a significant issue that requires further attention, particularly in the central region. To address these challenges, it is essential to increase investment in primary healthcare institutions, with a focus on strengthening pharmacist staffing, improving infrastructure, and enhancing the capacity of pharmacy services at the grassroots level.Keywords: pharmacists, health resource allocation, primary healthcare institutions, regional disparities, β convergence